The Effect of the Implementation of Corporate Governance and Profit Management with Credit Risk as Intervening Variables on the Financial Performance of Banking (Analytical Study on Commercial Banking and Sharia Banking Listed on the Indonesian Stock Exchange) - Khalisah Visiana; Nisa Bela (Budapest International Research and Critics University, 2022)
This study aims to determine whether Good Corporate Governance (GCG) affects the financial performance of conventional and Islamic banking companies listed on the IDX to determine whether earnings management affects the company's financial performance. Conventional and Sharia banking listed on the IDX, to determine GCG on credit risk in conventional and Sharia banking, to determine earnings management on credit risk in conventional and Sharia banking, to determine GCG effect on financial performance mediated by risk credit as an intervening variable in conventional and Islamic banking, to determine whether earnings management affects financial performance mediated by credit risk as an intervening variable in conventional and Islamic banking. The population used in this study are 43 conventional banking companies listed on the Indonesia Stock Exchange and using the purposive sampling method according to the criteria, there are 20 selected banking companies, using the 2016 to 2020 observation year (5 years), for the population in Islamic banking there are four banking companies with purposive sampling method according to the criteria there are four selected banks. From the results of hypothesis testing, it is known that the implementation of Good Corporate Governance (GCG) has a significant direct effect on Financial Performance (KK) in Islamic banking, and the implementation of Good Corporate Governance (GCG) with indicators of institutional ownership, the proportion of independent commissioners, the size of the board of commissioners and the audit committee. Significant effect on financial performance in conventional banking. However, mcg on indicators of ownership of directors has no significant effect on financial performance. Applying earnings management to financial performance has a significant effect on Islamic banking.